Open Medical Library: Cooperation and Scientific Communication Network through RSS - Alonso Arévalo, Julio (2009)
One of the fastest and most performing tools on Web 2.0 is RSS (Really Simple Syndication). It allows the access to digital content without constantly visiting the pages where it is stored. Syndication enables to share all kind of information in XML format, and offers us the opportunity of showing our own content in other web pages in an integrated way, giving an added value to the information. In this communication we would like to present a Network Collaborative Project between medical libraries belonging to different institutions, located in different geographical areas and with different purposes, objectives and interests (some of them focusing on research and teaching and other on medical practice). Our medical libraries have incorporated “the content syndication”, on the one hand, as another tool for medical librarian work and, on the other hand, as a value-added service in order to be useful to different users such as medical staff, teachers, researchers or students. RSS lets us share information channels, creating a space for collaborative research. Syndication is a great help to our users as it develops a new trend in the content management sector, which is changing considerably the relationship with information, for both users and librarians’ point of view.